Overview of vegetable seed production research in India - P.R. KUMAR; SHIV K.YADAV; SANDEEP KUMAR LAL; R.K. CHOWDHURY; M. DADLANI (Seed Research, 2026)
Although seed saving of traditional vegetable crops has been a domestic practice through the ages, planned cultivation of seeds came into vogue later. In the beginning, we used to rely fully on imports for quality seeds, but now we are exporting open pollinated as well as hybrid seeds of several vegetables. Efforts in public sector started soon after the independence, which still holds a major share of R&D in India. Indo-American Hybrid Seeds was the first indigenous private sector to introduce and popularise F, hybrid vegetables in India. As the cultivation of vegetable crops spread and exchange of seeds from one area to another started, the workers witnessed stresses of all kinds: biotic and abiotic. Therefore, emphasis was laid on production of resistant varieties and F, hybrids by combining different resistance genes from various available sources. The package of practices for most of the vegetable crops has been standardized. At the same time, information generated on floral biology and evolution of male sterility, self- incompatibility and other cross-pollination mechanisms encouraged the scientists as well as progressive farmers produce hybrid seed on commercial scale. India is about to enter into a new IPR regime to shortly. Hence, to meet the challenges of international market and to stand the provisions made in the new legislation, it is imperative to take a look of our achievements in the past and strengths as of now in order to mitigate the shortcomings before we barge into future.